1999
DOI: 10.1111/j.1574-6968.1999.tb13662.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial remediation of NTO in aqueous industrial wastes

Abstract: The bioremediation of aqueous wastes containing 5-nitro-1,2,4-triazol-3-one (NTO) was investigated. The microorganism used is a Bacillus licheniformis strain, isolated from the contaminated solutions by enrichment techniques. The biodegradation was carried out in the waste (15 g l-1 NTO) and proceeded through the nitroreduction of NTO, followed by the ring cleavage of the formed primary amine 5-amino-1,2,4-triazol-3-one (ATO). Both steps were optimized and according to the optimal conditions, the nitroreductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 20 publications
4
66
0
Order By: Relevance
“…Biotic (Le Campion et al, 1998a; Le Campion et al, 1999a; Krzmarzick et al, 2015; Richard and Weidhass, 2014) and abiotic (Le Campion et al, 1999b; Linker et al, 2015) degradation of NTO has been evaluated in a few recent studies. A bacterial strain, Bacillus licheniformis was used to degrade NTO in industrial wastewater (Le Campion et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Biotic (Le Campion et al, 1998a; Le Campion et al, 1999a; Krzmarzick et al, 2015; Richard and Weidhass, 2014) and abiotic (Le Campion et al, 1999b; Linker et al, 2015) degradation of NTO has been evaluated in a few recent studies. A bacterial strain, Bacillus licheniformis was used to degrade NTO in industrial wastewater (Le Campion et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…NTO is highly soluble (16,642.0 mg L À1 at 25 C) (Spear et al, 1989) and its transport to groundwater used as potable water source could result in human exposure to the chemical. While NTO showed low toxicity to the freshwater organism Ceriodaphnia dubia, green algae Selenastrum capricornutum (Haley et al, 2009), and Rana pipiens tadpoles (Stanley et al, 2015), it is a male reproductive toxicant in rats (Wallace, 2011;Lent et al, 2015) and was reported to form transformation products that can be toxic if they behave similarly to metabolic intermediates of other nitro-compounds (Le Campion et al, 1999b). Based on these risks, accurate soil adsorption coefficients (K d s) and transformation rate constants are necessary to simulate and predict NTO fate and transport to groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial transformation studies have shown that NTO can undergo nitroreduction under anaerobic conditions (Krzmarzick et al, 2015) and form 5-amino-1,2,4-triazol-3-one (ATO). ATO can further transform under aerobic conditions to CO 2 , urea, and inorganic nitrogen species (Le Campion et al, 1999b;Krzmarzick et al, 2015). Mark et al (2016) conducted a series of kinetic and equilibrium batch experiments to determine first order transformation rate constants (k), K d s and Freundlich adsorption coefficients (K f s) for NTO using multiple soils with a range of properties.…”
Section: Introductionmentioning
confidence: 99%
“…Its nitro group is reduced to an amino group, yielding 3-amino-1,2,4-triazol-5-one (ATO, Figure 1), which was found to be persistent in the soil in the absence of oxygen [57]. The reductive transformation of NTO to ATO could alter the molecule’s toxicity.…”
Section: Introductionmentioning
confidence: 99%